Redox status of serum apolipoprotein E and its impact on HDL cholesterol levels - Yamauchi, Kazuyoshi; Ebihara, Yuka; Kawakami, Yasushi (Clinical biochemistry, 2017)
Apolipoprotein E (apoE) is closely involved in the pathogenesis of apoE-related diseases, such as Alzheimer's disease and cardiovascular disease. The redox modulation of cysteine-thiols in a protein is involved in various pathophysiological regulations; however, that of apoE has not been studied in detail. Herein, we devised an analytical method to determine the redox status of serum apoE and assessed its relation to serum cholesterol levels and apoE phenotype. The present method was based on a band shift assay, using a photocleavable maleimide-conjugated polyethylene glycol. The basic characteristics of the present method were found to be satisfactory to determine the redox status of serum apoE quantitatively. Serum apoE was separated into its reduced-form (r-), non-reduced-form (nr-), apoE-AII complex, and homodimer using this method. R-apoE could be detected as a 40-kDa band, whereas nr-apoE remained as monomeric apoE. R-apoE displayed a preference for VLDL; however, the levels showed the correlation with HDL-cholesterol levels (p<0.005). Redox status of serum apoE was significantly different among apoE phenotypes. The quantitative ratios of nr-apoE to total apoE in serum from subjects with apoE4/E3 were higher than in serum from subjects with apoE3/E3 (p<0.0001) and apoE3/E2 (p<0.001). The redox status of serum apoE might be related to the synthesis of HDL. The information concerning the redox status of serum apoE provided by the present method may be a potent indicator to evaluate various apoE-related diseases. •An analytical method to determine the redox status of serum apoE is proposed.•Reduced-form apoE displays a preference of VLDL fraction.•The levels of reduced-form apoE show a significant correlation with HDL-C levels.•Redox status of serum apoE is different among apoE phenotypes.•Redox status of serum apoE may be a potent indicator to evaluate apoE-related diseases.